2020
DOI: 10.1002/wfs2.1392
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification against traffic in human beings

Abstract: The trafficking of human beings is one of the most heinous crimes on earth. Shamefully, human trafficking remains a lucrative business in 2020, just as it was thousands of years ago. The estimated astonishing number of victims would most likely surprise nonexperts. The prosecution of human trafficking is often difficult and requires the identification of victims. The fields of forensic anthropology and forensic odontology are of the highest value for this purpose. Forensic genetics is also of interest and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These convergence criteria on the forces are sufficient for geometry determination. The simulation of STM images was performed by applying the Tersoff–Hamann theory in a plane-wave basis set as implemented in the STMpw code . Visualization of simulated data was conducted using the Crystal Maker 10 software…”
Section: Methodsmentioning
confidence: 99%
“…These convergence criteria on the forces are sufficient for geometry determination. The simulation of STM images was performed by applying the Tersoff–Hamann theory in a plane-wave basis set as implemented in the STMpw code . Visualization of simulated data was conducted using the Crystal Maker 10 software…”
Section: Methodsmentioning
confidence: 99%
“…STM topographic images have been simulated within the Tersoff-Hamann approximation , using the method by Bocquet et al . as implemented in STMpw . Adsorption energies have been calculated as where E (mol), E (Au­(111)), and E (mol@Au­(111)) are the energies of the gas-phase molecule, the gold surface, and the supported molecule, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Emmons et al [51] examined the type of microbes found in each bone and their correlation to human DNA preservation. The post-mortem dominant taxa observed was the same as that found by Damann et al with a few discrepancies possibly due to the sequencing methodology.…”
Section: Skeletal Remainsmentioning
confidence: 99%
“…Furthermore, there were differences by relative quantity of cortical bone, so there appear to be influences on microbial communities by bone microstructure based on the available void space or nutritive differences. Clostridium, a well-known collagenase producer present in the human gut, was associated with a decrease in human DNA concentration, which might explain why the bones located near the gut provide the lowest DNA quantities; however, this hypothesis needs to be explored further with absolute abundance measurements and a larger sample [51].…”
Section: Skeletal Remainsmentioning
confidence: 99%